2010
DOI: 10.1111/j.1365-2966.2010.17099.x
|View full text |Cite
|
Sign up to set email alerts
|

Transit timing variation in exoplanet WASP-3b★

Abstract: Photometric follow-ups of transiting exoplanets may lead to discoveries of additional, less massive bodies in extrasolar systems. This is possible by detecting and then analysing variations in transit timing of transiting exoplanets. We present photometric observations gathered in 2009 and 2010 for exoplanet WASP-3b during the dedicated transit-timing-variation campaign. The observed transit timing cannot be explained by a constant period but by a periodic variation in the observations minus calculations diagr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(123 citation statements)
references
References 48 publications
8
109
6
Order By: Relevance
“…Among these claims, WASP-10b (Maciejewski et al 2011), WASP-5b (Fukui et al 2011), the intriguing case of HAT-P-13b, which was monitored also by TASTE (Pál et al 2011;Nascimbeni et al 2011b;Southworth et al 2012), and the subject of the present investigation: WASP-3b (Maciejewski et al 2010). A&A 549, A30 (2013) fourteen transits with the value predicted by a linear ephemeris, Maciejewski et al (2010) claimed the detection of a sinusoidal modulation with a period of P TTV 127.4 days and a semiamplitude of ∼0.0014 days 2 min. They interpreted this signal as the effect of an outer perturber, identifying three possible orbital solutions in the range 6−15 M ⊕ and P = 3.03−3.78 days.…”
Section: Introductionmentioning
confidence: 75%
“…Among these claims, WASP-10b (Maciejewski et al 2011), WASP-5b (Fukui et al 2011), the intriguing case of HAT-P-13b, which was monitored also by TASTE (Pál et al 2011;Nascimbeni et al 2011b;Southworth et al 2012), and the subject of the present investigation: WASP-3b (Maciejewski et al 2010). A&A 549, A30 (2013) fourteen transits with the value predicted by a linear ephemeris, Maciejewski et al (2010) claimed the detection of a sinusoidal modulation with a period of P TTV 127.4 days and a semiamplitude of ∼0.0014 days 2 min. They interpreted this signal as the effect of an outer perturber, identifying three possible orbital solutions in the range 6−15 M ⊕ and P = 3.03−3.78 days.…”
Section: Introductionmentioning
confidence: 75%
“…From RV surveys, ∼30% of planets are in multiple planet systems (including ones with RV trends; Butler et al 2006), while only five hot Jupiters are (HD 187123b, HIP 14810b, ups Andb, HAT-P-13b, and HD 217107b; Wright et al 2009;Hebrard et al 2010a); i.e., fewer than 10% of hot Jupiters are known to have companions within a couple AU. This relative deficit also shows up in the transit sample, where most attempts at detecting transit timing variations caused by close companions (Holman & Murray 2005;Agol et al 2005) have been unsuccessful (e.g., Rabus et al 2009;Csizmadia et al 2010;Hrudková et al 2010), except for, perhaps, Maciejewski et al (2010Maciejewski et al ( , 2011 and Fukui et al (2011).…”
Section: Observationsmentioning
confidence: 92%
“…In the case of OGLE-111b, Díaz et al (2008) claimed that the transit times were inconsistent with a linear ephemeris, but an analysis by Adams et al (2010) with additional transit observations found no evidence for TTVs or duration variations and pointed to systematic errors in previous photometry. Maciejewski et al (2010) and Fukui et al (2011) presented evidence for TTVs in the WASP-3 and WASP-5 systems, respectively, but cautioned that additional transits are necessary to confirm or refute the signal (Fukui et al 2011 expressed caution about unknown systematic effects). Maciejewski et al (2011) presented evidence for TTVs of WASP-10b, and they reported a two-planet orbital solution that fit the TTVs and radial velocities better than alternative orbital models they found, which was not achieved in prior work.…”
Section: Introductionmentioning
confidence: 99%